At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
The answer is going to be
5(x-2 ) ( x+6 )
Hopefully it’s right :) .
Simplifying
5x2 + -20x + -60
Reorder the terms:
-60 + -20x + 5x2 = 0
Solving
-60 + -20x + 5x2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '5'.
5(-12 + -4x + x2) = 0
Factor a trinomial.
5((-2 + -1x)(6 + -1x)) = 0
Ignore the factor 5.
Set the factor '(-2 + -1x)' equal to zero and attempt to solve:
Simplifying
-2 + -1x = 0
Solving
-2 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + -1x = 0 + 2
Combine like terms: -2 + 2 = 0
0 + -1x = 0 + 2
-1x = 0 + 2
Combine like terms: 0 + 2 = 2
-1x = 2
Divide each side by '-1'.
x = -2
Simplifying
X = -2
Set the factor '(6 + -1x)' equal to zero and attempt to solve:
Simplifying
6 + -1x = 0
Solving
6 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + -1x = 0 + -6
Combine like terms: 6 + -6 = 0
0 + -1x = 0 + -6
-1x = 0 + -6
Combine like terms: 0 + -6 = -6
-1x = -6
Divide each side by '-1'.
x = 6
Simplifying
x = 6
Solution
X= { -2 ,6 }
5(x-2 ) ( x+6 )
Hopefully it’s right :) .
Simplifying
5x2 + -20x + -60
Reorder the terms:
-60 + -20x + 5x2 = 0
Solving
-60 + -20x + 5x2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '5'.
5(-12 + -4x + x2) = 0
Factor a trinomial.
5((-2 + -1x)(6 + -1x)) = 0
Ignore the factor 5.
Set the factor '(-2 + -1x)' equal to zero and attempt to solve:
Simplifying
-2 + -1x = 0
Solving
-2 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + -1x = 0 + 2
Combine like terms: -2 + 2 = 0
0 + -1x = 0 + 2
-1x = 0 + 2
Combine like terms: 0 + 2 = 2
-1x = 2
Divide each side by '-1'.
x = -2
Simplifying
X = -2
Set the factor '(6 + -1x)' equal to zero and attempt to solve:
Simplifying
6 + -1x = 0
Solving
6 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + -1x = 0 + -6
Combine like terms: 6 + -6 = 0
0 + -1x = 0 + -6
-1x = 0 + -6
Combine like terms: 0 + -6 = -6
-1x = -6
Divide each side by '-1'.
x = 6
Simplifying
x = 6
Solution
X= { -2 ,6 }
Answer:
± [tex]\sqrt{-800}[/tex] / 2 or ±800i
Step-by-step explanation:
there are no rational roots because the square root of a negative
i got the answer by using the quadratic formula: (-b ±√b2 - 4ac) /2a
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.